Pengembangan Wisata Halal terhadap Sarana Prasarana dan Kesadaran Masyarakat di Gampong Ujong Muloh Kecamatan Indra Jaya - Tria Safitri; Atika Faradina; Siti Fatimah; Nili Roslina; Nurul Afrah; Muhammad Fathi Rizqi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This research is a qualitative descriptive study which describes the facts in the field related to the development of halal tourism on infrastructure and public awareness in Ujong Muloh Village, Indra Jaya District. The purpose of this study is to determine the effect of infrastructure and public awareness on the development of halal tourism and to see how the development of halal tourism on infrastructure and community awareness in the field. The primary data sources in this study include the results of interviews with the indigenous people of Ujong Muloh Village, documentation during the field, while the secondary data sources in this study include sources from the internet, books that have relevance to the focus of this research. The results of the study that the development of halal tourism on infrastructure and public awareness are closely related to each other, if one of them is not possible or even inadequate it will have an impact on holding halal tourism in Ujong Muloh Village.